Governing Discourses: Fear, “Security” and Symbolic Power - Camacho Monge, Daniel (2026)
In 2026, Latin America finds itself immersed in a process marked by the seizure of executive power—with a strong presence in the legislature in some cases—by ultra-neoconservative authoritarian forces, which have achieved this thanks to strong electoral support. I have proposed a thesis in which I intend to establish a relationship, not of determining causality, but rather of a high degree of influence of the nation-state's economic and social structure on its political regime (Paper for the Congress of the Latin American Sociological Association in Rio de Janeiro this coming July). These are very similar regimes, headed by leaders who are also very similar to one another. Therefore, it is plausible to seek part of their explanation in profound processes that unfold within the social structure, processes that are not local, but rather generalized and shared, occurring not only in Latin America but throughout the Americas and in Europe. I propose and explore the hypothesis that this widespread and shared dynamic is related to the important analytical category of accumulation. In short, it is argued that the type of accumulation in the current historical period is characterized by its transnational nature, making it functional for a political regime lacking significant democracy and exhibiting considerable authoritarian practices.